Syvertsenia iberica (Cymatosiraceae): a new estuarine diatom genus characterized by the position of its process - Gomes, Ana; Witkowski, Andrzej; Dąbek, Przemysław; Boski, Tomasz; Moura, Delminda; Szkornik, Katie; Kurzydłowski, Krzysztof (Phytotaxa, 2013)
Diatom assemblages were studied along an intertidal transect in the lower Guadiana River Estuary (South-Eastern Portugal). The analyses of the assemblages by means of light and scanning electron microscope revealed a new diatom genus and species, Syvertsenia iberica. Syvertsenia was found in three out of eighteen of the samples analysed in the transect.  The proposed new genus belongs to the family Cymatosiraceae, which is characterized by the presence of two distinct ocelluli. In common with other genera belonging to the subfamily Cymatosiroideae, the new genus shows heterovalvy and morphological similarity to Cymatosira, Campylosira and Plagiogrammopsis. In terms of ultrastructure, the features which identify these diatoms as a new genus are its linear valve outline, protracted to distinctly set off apices and also the distribution pattern of areola. Furthermore the position of the tubular process on a valve mantle extension, allows an easy distinction from other Cymatosiroideae. Syvertsenia iberica is a benthic epipsammic diatom whose ecological and geographical distribution requires more investigation.